Suvorexant, a Novel Dual Orexin Receptor Antagonist, for the Management of Insomnia - Andrew H. Han; Caroline R. Burroughs; Evan P. Falgoust; Jamal Hasoon; Grace Hunt; Juyeon Kakazu; Tim Lee; Adam M. Kaye; Alan D. Kaye; Latha Ganti (Health Psychology Research)
# Purpose of Review